Factores materno infantil y anemia en lactantes en la institución prestadora de servicios de salud Bellavista Nanay de Iquitos 2021 - Pinchez Torres, Patricia (2023)
The objective of the study was to determine the relationship between maternal and infant factors and anemia in infants of the Institución Prestadora de Servicios de Salud I-4 Bellavista Nanay, in the city of Iquitos, 2021. The type of study was observational, descriptive, cross-sectional, retrospective; the study design was non-experimental, correlational; the sample consisted of 169 mothers of infants from 1 to 11 months and 29 days of age. A questionnaire was used and the Pearson coefficient obtained an acceptable validity of 89%. The results showed that 54.4% of infants had anemia; with respect to maternal factors that presented a significant statistical relationship were the degree of secondary education (p=0.001) and the lower socioeconomic level (p=0.023); with respect to infant factors that presented a significant statistical relationship were the degree of secondary education (p=0.001) and the lower socioeconomic level (p=0.023); with respect to infant factors that presented a significant statistical relationship (p=0.023). The study concluded that there is a significant statistical relationship between maternal and infant factors and anemia in infants at the Bellavista Nanay Health Services Provider Institution IPRESS I-4, in the city of Iquitos, 2021.